The training needs of female mathematics teachers in light of the Integrative Approach between science, technology, engineering and mathematics (STEM) in Al-Khobar - Aldobyan, Ahood Hamad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to determine the degree of training needs in light of the integration approach between science, technology, engineering and mathematics (STEM) for mathematics teachers in Khobar. To achieve this goal, the descriptive survey approach was used through the study tool (a questionnaire) consisting of (20) standards of teaching practices in three areas (planning, implementation and evaluation) that were built in their final form based on a list of teaching practices in light of STEM and through the literature and the previous studies. Then after making sure of their apparent and internal validity and stability, the questionnaire was applied to a randomly selected sample of (180) female mathematics teachers in Khobar. The study found that the degree of training need for mathematics teachers in light of the STEM approach was highly in the three areas (planning, implementation, and evaluation), and there were no statistically significant differences between the responses of the study sample attributed to the educational qualification or the educational stage in which the teacher is taught, while differences appeared Statistical significance attributed to the number of years of experience and the number of training programs. The study recommended the necessity of increasing the culture of male and female teachers at STEM, and making use of the results of this study in building specialized training programs for teaching practices in light of STEM for mathematics teachers, And preparing academic content or intensive workshops in colleges of education for pre-service mathematics teachers to acquire teaching practices in planning, implementation and evaluation in light of the STEM approach.
Keywords: Training needs; teaching practices; STEM; female mathematics teachers